Heavy metal contamination in the soil and Taal Lake Post-Taal Volcano eruption - Banta, Genevee; Salibay, Cristina (PT Mattawang Mediatama Solution, 2023)
Volcanic eruption can be a source of heavy metal contamination in the environment and such contamination may cause certain risks to the environment and to those who are exposed to the volcanic contents. This study aimed to assess the agricultural soil for heavy metal contamination after the 2020 Taal volcano eruption. The agricultural soil samples were collected from Cuenca and Talisay, Batangas and Tagaytay City, Cavite and were submitted to a laboratory for arsenic, cadmium and mercury detection and quantification. The detected metal concentrations were compared to the standard values of the Department of Environmental and Natural Resources for arsenic and United States Environmental Protection Agency for cadmium and mercury for soil samples while for the water samples, the standard values of Department of Environment and Natural sources were used. The soil from Talisay, Batangas had two-fold arsenic increase while the samples from Tagaytay City, Cavite had one-fold elevation. Cadmium and mercury in the soil and water were within the acceptable level in the three municipalities. The arsenic contamination of the soil post-volcanic eruption was probably due to the direction of the wind during the eruption, the amount of ashfall and groundwater contamination. Heavy metal contamination can be detected years after the eruption.